Association between Asymptomatic Unilateral Internal Carotid Artery Stenosis and Electrophysiological Function of the Retina and Optic Nerve - Anna Machalińska; Aleksandra Kowalska-Budek; Miłosz Piotr Kawa; Arkadiusz Kazimierczak; Krzysztof Safranow; Marta Kirkiewicz; Grażyna Wilk; Wojciech Lubiński; Piotr Gutowski; Bogusław Machaliński (Journal of Ophthalmology)
Purpose. This study was designed to assess retinal and optic nerve bioelectrical function in patients with unilateral asymptomatic but hemodynamically significant internal carotid artery stenosis (ICAS). Methods. Forty-two subjects with a diagnosis of unilateral ICAS and 34 controls were analyzed. Full-field electroretinogram (ERG), pattern electroretinogram (PERG), and pattern visual-evoked potentials, as well as optical coherence tomography and ophthalmological examination, were performed. Data analysis included eyes ipsilateral to ICAS (EIS) and eyes contralateral to ICAS (ECS). Results. Intraocular pressure was significantly decreased in EIS and ECS compared to that in the controls. In the macula, both the cube average thickness and cube volume values were significantly reduced both in EIS and ECS compared to those in the controls. Similarly, PERG P50 and N95 wave amplitudes were significantly smaller in EIS and ECS compared to those in the controls. The ERG rod b-wave and rod-cone a-wave amplitudes were decreased, and implicit times were significantly prolonged, whereas the OP wave index was reduced in EIS compared to that in the controls. No differences in IOP, OCT, or ERG and PERG parameters were identified between EIS and ECS. Conclusions. Our study demonstrated that retinal bioelectrical function is negatively affected by ICAS despite the absence of objective clinical signs and symptoms of ocular ischemia.